2023
DOI: 10.1051/0004-6361/202244909
|View full text |Cite
|
Sign up to set email alerts
|

Tdcosmo

Abstract: When strong gravitational lenses are to be used as an astrophysical or cosmological probe, models of their mass distributions are often needed. We present a new, time-efficient automation code for the uniform modeling of strongly lensed quasars with GLEE, a lens-modeling software for multiband data. By using the observed positions of the lensed quasars and the spatially extended surface brightness distribution of the host galaxy of the lensed quasar, we obtain a model of the mass distribution of the lens galax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 98 publications
0
16
0
Order By: Relevance
“…First, we model the light of the lens galaxy with two Sérsic profiles, and the light of multiple lensed SN images by fitting a PSF model constructed from multiple stars in the field of the drizzled data. Ertl et al (2023) showed that for lensed quasars we can achieve astrometric accuracy of 2 mas from the surface brightness (SB) fit, by comparing the modeled image positions to those measured by the Gaia satellite. We use our SN image positions (from PSF fitting) to constrain the mass parameters, since we did not find (and do not expect) any substantial lensed arc light (from the SN host galaxy) in the modeling residuals of the three UVIS bands.…”
Section: A2 Results Based On Sn Image Positionsmentioning
confidence: 99%
See 3 more Smart Citations
“…First, we model the light of the lens galaxy with two Sérsic profiles, and the light of multiple lensed SN images by fitting a PSF model constructed from multiple stars in the field of the drizzled data. Ertl et al (2023) showed that for lensed quasars we can achieve astrometric accuracy of 2 mas from the surface brightness (SB) fit, by comparing the modeled image positions to those measured by the Gaia satellite. We use our SN image positions (from PSF fitting) to constrain the mass parameters, since we did not find (and do not expect) any substantial lensed arc light (from the SN host galaxy) in the modeling residuals of the three UVIS bands.…”
Section: A2 Results Based On Sn Image Positionsmentioning
confidence: 99%
“…For each band, we use the image positions reported in Table 7 and adopt an uncertainty on the image positions of 4 mas to constrain the lens mass parameters. The 4 mas uncertainty is an estimate based on the astrometric accuracy of 2 mas (Ertl et al 2023) and to account for substructure lensing, which can perturb the image positions at the few milliarcseconds level, as shown by Chen et al (2007). We impose uniform priors on all eight lens mass parameters that are tabulated in the leftmost column of Table 9.…”
Section: A2 Results Based On Sn Image Positionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter is the best match to our networks, and is comparable in performance, as mentioned in S21a. There is also currently a lot of work going into automated modeling without machine learning (e.g., Nightingale et al 2018Nightingale et al , 2021Rojas et al 2022;Savary et al 2022;Ertl et al 2023;Etherington et al 2022;Gu et al 2022;Schmidt et al 2023), which typically performs better than neural networks but requires significantly longer run times of hours to days. We refer to Schuldt et al (2022) for a direct comparison between the network presented here and traditionally obtained models for real HSC lenses.…”
Section: Network Results and Performancementioning
confidence: 99%